The Indonesian Self-Efficacy Questionnaire for Children: Translation, Cross-Cultural Adaptation, and Psychometric Evaluation - Wuryaningsih, Emi Wuri; Lusmilasari, Lely; Haryanti, Fitri; Wahyuni, Budi (Universitas Airlangga, 2025)
Introduction: This study aimed to translate and validate the Self-Efficacy Questionnaire (SEQ-C) and its subscale for Indonesian adolescents, which has potential implications for bullying prevention. Methods: Cross-cultural adaptation was carried out using the Beaton guidelines. An assessment of psychometric testing was carried out during January and February 2024. The eligibility criteria for participants were students aged 13 to 15. Students who declined to participate were excluded. The research involved 120 children. Testing the questionnaire's structural factors used Confirmatory Factor Analysis (CFA). IBM SPSS 25 and AMOS 29 were used for the analysis. Results: Following the criteria established for CFA, two items (ASE10 and SSE18) were eliminated due to their low factor loadings. This resulted in a refined SEQ-C structure of 22 items distributed across three factors. The alpha reliability coefficients showed robust internal consistency for the entire scale at first test and retest (α=0.884; α =0.911) and for each of the three subscales (all >0.80). The model fit indices indicated satisfactory values for the Comparative Fit Index (CFI)=0.906; Root Mean Square Error of Approximation (RMSEA)=0.063; and the Minimum Discrepancy Function by Degrees of Freedom divided (CMIN/DF)=1.474). Conclusion: The SEQ-C emerges as a trustworthy and valid tool for evaluating self-efficacy across three key components: intellectual, social, and emotional. It can assess adolescent self-efficacy for research, education, and nursing interventions, as part of enhancing the life skills of adolescents.